An application of deviance regulation theory to organ donation promotion. Issue 5 (19th October 2020) - Reynolds-Tylus, Tobias
ABSTRACT: Deviance regulation theory proposes that when a behavior is seen as common, a loss-frame message should be more effective; conversely, when a behavior is seen as uncommon, a gain-frame message should be more effective. The current study tests deviance regulation theory in the context of organ donation promotion. Non-donors ( N = 386) were randomly assigned to view messages in a 2 (norm: high vs. low) x 2 (frame: gain vs. loss) factorial design. Dependent variables included behavioral intention and information seeking. Results were inconsistent with deviance regulation theory's proposed interaction between norm and message frame. Rather, there was a main effect such that participants who read a low norm message engaged in greater information seeking than those who read a high norm message. Notably, the high norm message was seen as less believable than the low norm message. The theoretical and practical implications of these findings are discussed.